Input-output linkages and monopolistic competition: Input distortion and optimal policies - Benjamin Jung; Wilhelm Kohler (Universität Hohenheim, Fakultät Wirtschafts- und Sozialwissenschaften, 2021)
In this paper, we provide a detailed analysis of a mechanism that distorts production towards too much use of primary factors like labor and too little use of intermediate inputs. The distortion results from two ingredients that are cornerstones of modern quantitative trade theory: monopolistic competition and input-output linkages. The distortion as such is unrelated to trade, but has important consequences for trade policy, including a positive first-order welfare effect from an import subsidy. For a crystal-clear view on the distortion, we first look at it in a single-sector, closed economy where the monopolistic competition equilibrium would be efficient without the presence of input-output linkages. We compare the social-planner-solution with the decentralized market equilibrium, and we identify first-best policies to correct the distortion. To analyze the trade policy implications we then extend our analysis to a setting with trade between two symmetric countries. We identify first-best cooperative policies, featuring nondiscriminatory subsidies of intermediate input use, aswell as non-cooperative trade policies where countries use tariffs to weigh terms of trade effects against benefits from correcting the input distortion.
urn:nbn:de:bsz:100-opus-19375
Keywords: F12; F13; D57; D61; H21; 330; input-output linkages; monopolistic competition; international trade; allocational inefficiency; optimal policy